Nanocomposites of polyhydroxyurethane with nanocrystalline cellulose: Synthesis, thermomechanical and reprocessing properties. (15th April 2021) - Ge, Wenming; Zhao, Bingjie; Li, Lei; Nie, Kangming; Zheng, Sixun
Graphical abstract: A novolac epoxide-based five-membered cyclic carbonate (NE5CC) was successfully synthesized and used as the precursor to polyhydroxyurethane thermoset. To improve the thermomechanical properties of the thermoset, poly( N -vinylpyrrolidone)-grafted nanocrystalline cellulose (denoted NCC-PVPy) was synthesized to incorporate into the PHU thermosets. Highlights: Novolac epoxide was used to synthesize precursor of polyhydroxyurethane thermoset. Nanocrystalline cellulose was incorporated into the thermoset to obtain nanocomposites. The nanocomposites displayed improved thermomechanical properties. The nanocomposites possessed shape memory and reprocessing properties. Abstract: A commercial novolac epoxide was used to react with carbon dioxide (CO2 ), to obtain a novel five-membered cyclic carbonate. This novel novolac epoxide-based five-membered cyclic carbonate (NE5CC) was successfully utilized to prepare polyhydroxyurethane (PHU) thermoset. To improve the thermomechanical properties of the PHU thermoset, nanocrystalline cellulose (NCC) was used as the modifier. To facilitate dispersion of the modifier, the surface of NCC was functionalized with poly(N-vinylpyrrolidone) (PVPy). The functionalized NCC (NCC-PVPy) was prepared via the surface-initiated reversible addition-fragmentation chain transfer (RAFT) polymerization of N-vinylpyrrolidone (NVP). It was found that NCC-PVPy was readily dispersed in PHU matrix in the form of single nanocrystals. The nanocomposites of PHU with NCC displayed the enhanced glass transition temperatures and improved mechanical properties. In the meantime, the nanocomposites had good shape recovery properties; the nanocomposites can be reprocessed at elevated temperature. The reprocessing properties can be utilized to reprogram the original shapes of the shape memory nanocomposites.